Equity or equality: outer and expanding circle teachers' awareness of and attitudes towards World Englishes and international proficiency tests. Issue 10 (26th November 2022) - Monfared, Abbas
ABSTRACT: This paper investigates the attitudes of 246 English teachers from Outer and Expanding Circles (EC and OC) towards the global spread of English and the challenges underpinning international proficiency tests. Using a questionnaire, supplemented with interviews with a smaller group of teachers, this study explores how EC and OC teachers perceive the relevance of World Englishes (WE) to the international tests like the TOEFL and IELTS and what implications their views have in English language teaching. Using quantitative and qualitative research instruments, the results of the study show a theory-practice gap in the views of the participants. While the majority of the participants were in favour of WE in theory, they were actually against the acceptance of WE norms in the international proficiency tests for different reasons such as their concerns for standards in language testing, equality, test fairness and test-takers' tendency toward international tests. The results of this study indicate that, together with supporting different varieties of English, it is important to find ways to raise awareness of teachers and learners of the existence of diversity in the landscape of English.